Digital Transformation in Small and Medium Enterprises: A Qualitative Study of Adoption Challenges and Strategies - Simorangkir, Yosua Novembrianto; Nuryanti, Yulis; Suroso, Suroso; Iskandar, Joni; Pebrina, Erni Taruli (AGUSPATI RESEARCH INSTITUTA, 2025)
Digital transformation has become a strategic necessity for Small and Medium Enterprises (SMEs), yet its implementation remains uneven due to complex technological, organizational, and contextual barriers. This study explores how SMEs navigate the challenges of adopting digital technologies and the strategies they employ to adapt within resource-constrained environments. Using a qualitative multi-case study approach, data were collected through semi-structured interviews, observations, and document analysis involving SMEs across diverse sectors. The findings reveal that technological limitations—such as inadequate infrastructure and high software costs—intersect with financial constraints to restrict the scope of digital adoption. Organizational readiness and human resource capability further influence transformation outcomes, with limited digital literacy and resistance to change emerging as significant inhibitors. Despite these challenges, SMEs demonstrate adaptive resilience by adopting incremental digitization, leveraging collaborative networks, and aligning digital initiatives with their operational contexts. Leadership commitment and capability-building efforts also play crucial roles in shaping transformation pathways. The study contributes to theoretical discourse by extending the relevance of the Technology–Organization–Environment (TOE) framework and the Resource-Based View (RBV) within emerging-market SME contexts. Practically, the findings underscore the need for targeted support systems, affordable digital solutions, and capacity-building programs to enable inclusive digital transformation.